The association between culture positivity and long-term mortality in critically ill surgical patients - Yu-Cheng Wu; Li-Ting Wong; Chieh-Liang Wu; Wen-Cheng Chao (Journal of Intensive Care, 2021)
Abstract Background The long-term outcome is an essential issue in critically ill patients, and the identification of early determinant is needed for risk stratification of the long-term outcome. In the present study, we investigate the association between culture positivity during admission and long-term outcome in critically ill surgical patients. Methods We linked the 2015–2019 critical care database at Taichung Veterans General Hospital with the nationwide death registration files in Taiwan. We described the long-term mortality and proportion of culture positivity among enrolled subjects. We used a log-rank test to estimate survival curves between patients with and without positive cultures and a multivariable Cox proportional hazards regression model to determine hazard ratio (HR) and 95% confidence interval (CI). Results A total of 6748 critically ill patients were enrolled, and 32.5% (2196/6749) of them died during the follow-up period, with the overall follow-up duration was 1.8 ± 1.4 years. We found that 31.4% (2122/6748) of critically ill patients had at least one positive culture during the index admission, and the number of patients with positive culture in the blood, respiratory tract, urinary tract, skin and soft tissue and abdomen were 417, 1702, 554, 194 and 139, respectively. We found that a positive culture from any sites was independently associated with high long-term mortality (aHR 1.579, 95% CI 1.422–1.754) after adjusting relevant covariates, including age, sex, body-mass index, comorbidities, severity score, shock, early fluid overload, receiving mechanical ventilation and the need of renal replacement therapy for critical illness. Conclusions We linked two databases to identify that a positive culture during admission was independently correlated with increased long-term mortality in critically ill surgical patients. Our findings highlight the need for vigilance among patients with a positive culture during admission, and more studies are warranted to validate our findings and to clarify underlying mechanisms.